A US strategy for IFRS adoption. Response to the US SEC's public consultation - Nicolas Véron (Bruegel, 2009)
The US Securities and Exchange Commission has conducted a public consultation on a 'roadmap' it proposed late last year to adopt International Financial Reporting Standards in America. This debate takes particular relevance as the crisis has highlighted the importance of accounting standards as an instrument of economic policymaking, with a high-profile controversy about 'mark-to-market' accounting. Nicolas Véron responds with suggestions about how the SEC should both support IFRS, and push for reforms of standard-setting governance and globally consistent enforcement.
Keywords: 330; International Financial Reporting Standards; Grundsätze ordnungsmäßiger Buchführung; USA